Cost-Effective Prosthetic Hand for Amputees: Challenges and Practical Implementation - Sujana, Iylia Nabila; Abdul Sukor, Jumadi; Jalani, Jamaludin; Ngerong Sali, Frankie; Mohd Rejab, Sujana (International Journal of Integrated Engineering, 2023)
According to statistics, approximately 160,000 people in Malaysia, out of the current population of 32 million, need prosthetic or orthotic equipment. For individuals who have experienced upper extremity amputations, significant challenges are posed by the loss of functionality and the desire for a cosmetically appealing solution. To address this issue, a cost-effective prosthetic hand was proposed and developed. An overview of existing prosthetic hands is also offered, with an emphasis on cost-effectiveness, challenges, strengths, and weaknesses. The developed prosthetic hand incorporates a practical and underactuated finger mechanism. It is equipped with controllers based on EMG sensors to ensure that optimal responses are achieved during the grasping and releasing of objects. A suitable motor was carefully chosen to facilitate effective grasping and ungrasping activities. The proposed design was realized using SolidWorks and a 3D Printer. The capabilities of the prosthetic hand were demonstrated through a series of tests involving various objects, including pliers, a screwdriver, and a phone. The results indicate that objects of different sizes and shapes can be effectively grasped and ungrasped by the prosthetic hand. The unique bending angles in each finger result from the way tendons are connected via flexible cords and fishing lines to the servo motor. This design allows for a dynamic response based on the user's muscle flex and strength. The affordability of this cost-effective prosthetic hand demonstrates its potential as a practical and viable solution for amputees aiming to restore their grasping functionalities.